A(n) = -6 +(n-1)1/5

Here

A(n) is the nth term

First term a = -6

Different d = 1/5

Term n = n

For first term n = 1

A(n) = -6 +(n-1)1/5

A(1) = -6 +(1-1)1/5

A(1) = -6 +(0)1/5

A(1) = -6 +0

A(1) = -6

So first term = -6

Fourth term n = 4

A(n) = -6 +(n-1)1/5

A(4) = -6 +(4-1)1/5

A(4) = -6 +(3)1/5

A(4) = -6 +3/5

A(4) = (-30+3)/5

A(4) = (-27)/5

So fourth term = -27/5

Tenth term n = 10

A(n) = -6 +(n-1)1/5

A(10) = -6 +(10-1)1/5

A(10) = -6 +(9)1/5

A(10) = -6 +9/5

A(10) = (-30+9)/5

A(10) = (-21)/5

So tenth term = -21/5

Here

A(n) is the nth term

First term a = -6

Different d = 1/5

Term n = n

For first term n = 1

A(n) = -6 +(n-1)1/5

A(1) = -6 +(1-1)1/5

A(1) = -6 +(0)1/5

A(1) = -6 +0

A(1) = -6

So first term = -6

Fourth term n = 4

A(n) = -6 +(n-1)1/5

A(4) = -6 +(4-1)1/5

A(4) = -6 +(3)1/5

A(4) = -6 +3/5

A(4) = (-30+3)/5

A(4) = (-27)/5

So fourth term = -27/5

Tenth term n = 10

A(n) = -6 +(n-1)1/5

A(10) = -6 +(10-1)1/5

A(10) = -6 +(9)1/5

A(10) = -6 +9/5

A(10) = (-30+9)/5

A(10) = (-21)/5

So tenth term = -21/5